Effects of Water–Fertilizer–Gas Coupling on Emitter Clogging and Uniformity of Drip Irrigation System - Peng Li; Xinkun Wang; Chenjun Zhang; Keyue Chen; Abdul Rahim Junejo; Jinrui Liu; Hao Li (Horticulturae)
The drip emitter is a fundamental component of the drip irrigation system, and its performance directly influences the efficiency of water–fertilizer–gas (WFG) coupling irrigation. However, the precise mechanism through which WFG coupling affects emitter clogging and system uniformity remains unclear. To address this, this study conducted a hydraulic performance test of the drip irrigation system based on micro-nano aerated drip irrigation technology. The clogging patterns of emitters and system uniformity were compared and analyzed under non-aerated drip irrigation and WFG coupling drip irrigation conditions. The results indicate that WFG coupling significantly alters the micromorphological structure and microbial diversity of clogged emitters. This change reduces clogging and can delay the clogging process of different types of emitters, thereby extending their service life by up to 29%. Additionally, it effectively improves the uniformity of the drip irrigation system. These findings highlight the potential of WFG coupling as an effective strategy to mitigate emitter clogging and optimize drip irrigation system performance.